Bulb yield and economic viability of onion in response to sulfur fertilization - Lacerda,Rodolfo R. de A. (2022)
ABSTRACT The cultivation of onion in the Brazilian Northeast region has been gaining prominence due to the favorable edaphoclimatic conditions and the use of technology. However, the increase in production costs, price fluctuations and the suppression of sulfur in fertilizer formulations constitute a risk for the farmers. Thus, the aim of this study was to evaluate the productive and economic aspects of onion production as a response to sulfur fertilization. Two experiments were carried out from June to November 2018 and 2019, at the Rafael Fernandes Experimental Farm, belonging to the Universidade Federal Rural do Semi-árido, in the municipality of Mossoró, Rio Grande do Norte, Brazil, in an Ultisol. The experimental design was randomized complete blocks with 14 treatments and four replicates, corresponding to the combination of two onion cultivars and seven doses of sulfur. The following characteristics were evaluated: sulfur content in the diagnostic leaf, bulb yield, total operating costs, gross revenue, net revenue, rate of return and yield index. Regardless of the cultivar, input costs add up to higher expenses, reaching approximate values of 60.6 and 48.4% of the total operating cost for the Rio das Antas and IPA 11 cultivars, respectively. Rio das Antas was more sulfur efficient, achieving greater bulb yield and net revenue. The 34 kg ha-1 sulfur dose promoted maximum yield and net revenue for Rio das Antas. The application of sulfur did not influence the yield of the IPA 11 cultivar.